Financial Literacy and Inclusion for Millennial UMKM Owners In West Jakarta - Rudolf Lumbantobing; Lambok DR Tampubolon; Deni Iskandar; Eka Desy Purnama; Diana Frederica (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The results of the Bank Indonesia survey show that there is still a low number of households that have savings accounts in banks. In addition, the number of households that can access loans at banks is also still very low. One of the problems that exist due to lack of financial knowledge so that not many people understand how to access loans in banks. For an entrepreneur or micro, small and medium enterprises are needed financial litersasi in order to easily get business capital from the bank. The purpose of this community service activity is to provide additional insight into how to plan and manage finances so that micro, small and medium enterprises, especially in West Jakarta, increase. The method of implementation of community service activities consists of three stages, namely preparation, implementation, evaluation and follow-up. The results of this activity provide solutions for Micro, Small and medium enterprises in West Jakarta on how to conduct comprehensive financial planning and management, analyze financial statements, and maintain cash flow position by identifying sources of cash receipts and expenditures.